ANALISIS TERHADAP MASALAH PENETAPAN NILAI GANTI RUGI DALAM RANGKA PEMBEBASAN TANAH UNTUK PEMBANGUNAN JALAN TOL KUNCIRAN-SERPONG (STUDI KASUS: PUTUSAN PENGADILAN NEGERI TANGERANG NOMOR 333/Pdt.G/2018/PN.Tng. Jo. PUTUSAN MAHKAMAH AGUNG NOMOR 3049 K/Pdt/2018) - Raymond Aristyo; Hasni Hasni (Jurnal Hukum Adigama, 2019)
Infrastructure development for the public interest is indeed very urgent to be held immediately given that some infrastructure development facilities are still very alarming so that it becomes a priority in the development program. In addition, land acquisition for public interest development is supported by high population growth and increased community aspirations and improved development for the public interest which continues to increase. Filling land for development in the public interest, valuation of compensation by appraisers is carried out per field, parcels of land and underground land, buildings, plants, objects related to land, or other losses that can be shared. In carrying out activities, the appraiser is guided by standards, while in carrying out his duties the appraiser approves the code of ethics. In the evaluation of community change, weak decisions that cannot be refused by the government asking for land, like it or not, like it or not the community requires land to the government, the community must accept and leave the environment where they were raised, returned and memories of their homes. Related to the writer interested in doing an analysis of the problem of determining the value of compensation in the framework of land acquisition for the construction of the Kunciran-Serpong toll road. This analysis is carried out using normative research methods with the aim of appealing to the principles of law and searching for theoretical scientific truths of the problems discussed.